Teletandem and project pedagogy in language and culture learning: Challenges and perspectives in new practices of virtual exchange - Rejane M. Gonçalves Maia; Francisco J. Quaresma de Figueiredo (Revista Lengua y Cultura)
This article outlines an online language learning initiative that introduced teletandem sessions (Telles, 2009) into the curriculum of the Modern Languages Degree Program at the Universidade Federal de Goiás (UFG), Brazil. In the first semester of 2023, the teletandem course brought together participants from Brazil, Argentina, and Ecuador. As Salomão (2020) asserts, teletandem is an internationalization at home action that has emerged in the last two decades as a potent methodology to enhance additional language learning processes through online interactions. It involves two students from different countries and cultural backgrounds who actively assist each other in learning their languages using virtual tools (Telles, 2015). The participants were also tasked with developing a project on a chosen theme, incorporating perspectives from the Brazilian, Ecuadorian, and Argentine contexts. They were equipped with theoretical and practical knowledge on applying project-based pedagogy in learning. Like teletandem, project pedagogy is also anchored in the theories of collaboration and socio-interactionism. It presupposes a new culture of learning that advocates for students to get involved in collaborative knowledge-building by carrying out transdisciplinary projects that problematize real life (Hernández, 1998). This research investigated possible challenges in combining project pedagogy and teletandem and verified how this combination can enhance the collaborative learning of languages and cultures. The data for this case study (Nunan, 1992) was obtained through video recordings of interactions during the classes and interviews with two pairs of students, among others. The results show that teletandem interactions promoted rich opportunities for participants to improve their language learning process. However, they needed help in managing the interaction time. So, the projects they developed about cultural aspects served as a guiding line for their conversations, making the interactions more objective and livelier.